2015
DOI: 10.1080/15592294.2015.1113798
|View full text |Cite|
|
Sign up to set email alerts
|

Increased DUX4 expression during muscle differentiation correlates with decreased SMCHD1 protein levels at D4Z4

Abstract: Facioscapulohumeral muscular dystrophy is caused by incomplete epigenetic repression of the transcription factor DUX4 in skeletal muscle. A copy of DUX4 is located within each unit of the D4Z4 macrosatellite repeat array and its derepression in somatic cells is caused by either repeat array contraction (FSHD1) or by mutations in the chromatin repressor SMCHD1 (FSHD2). While DUX4 expression has thus far only been detected in FSHD muscle and muscle cell cultures, and increases with in vitro myogenic differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 41 publications
5
73
0
Order By: Relevance
“…Differences Between FSHD 1 and 2 FSHD1 and 2 have the same downstream disease mechanism, DUX4 derepression, yet there are some unique epigenetic responses with respect to the underlying genetic mechanism upstream. In FSHD2 but not in FSHD1, PRC2-mediated H3K27 trimethylation of D4Z4 seems to play a role in the disease [36]. This might have implications for drug development, depending on which target is chosen.…”
Section: The Role Of the Stage Of Cell Development And Dux4 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences Between FSHD 1 and 2 FSHD1 and 2 have the same downstream disease mechanism, DUX4 derepression, yet there are some unique epigenetic responses with respect to the underlying genetic mechanism upstream. In FSHD2 but not in FSHD1, PRC2-mediated H3K27 trimethylation of D4Z4 seems to play a role in the disease [36]. This might have implications for drug development, depending on which target is chosen.…”
Section: The Role Of the Stage Of Cell Development And Dux4 Expressionmentioning
confidence: 99%
“…Furthermore, it has been shown that SMCHD1 protein levels decrease during muscle cell differentiation, correlating with DUX4 expression. Hence, differentiated muscle cells might be particularly prone to incomplete D4Z4 repression [36].…”
Section: The Role Of the Stage Of Cell Development And Dux4 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A muscle cell contribution to DUX4 in FSHD muscle biopsies is also likely, but via dynamic, stochastic DUX4 expression rather than the continuous expression seen in lymphocytes 32,40 . Time points for these transient bursts of DUX4 expression could include in satellite cells, when DUX4 expression may interfere with the normal function of the transcription factor PAX7 19,23,24 , and during myogenic differentiation, where DUX4 target gene expression may interfere with normal myogenesis 32,40,48 . Here we provide evidence for transient DUX4 expression at both these time points.…”
Section: Discussionmentioning
confidence: 99%
“…[120][121][122] FSHD1 is caused by a distinctive molecular mechanism affecting the subtelomeric region of chromosome 4q35 leading to DUX4 expression. 123,124 A large number of muscle MRI studies have been performed in patients with FSHD. [125][126][127][128][129][130][131] On MRI, the earliest and most affected muscles are the trapezius and serratus anterior followed by the latissimus dorsi and pectoralis major.…”
Section: Imaging and Pathological Correlationsmentioning
confidence: 99%